Common evolutionary features of the envelope glycoprotein of HIV-1 in patients belonging to a transmission chain - Beretta, Maxime (Sci Rep, 2020)
The diversity of the HIV-1 envelope glycoproteins (Env) is largely a consequence of the pressure exerted by the adaptive immune response to infection. While it was generally assumed that the neutralizing antibody (NAb) response depended mainly on the infected individual, the concept that virus-related factors could be important in inducing this response has recently emerged. Here, we analyzed the influence of the infecting viral strain in shaping NAb responses in four HIV-1 infected subjects belonging to a transmission chain. We also explored the impact of NAb responses on the functional evolution of the viral quasispecies. The four patients developed a strong autologous neutralizing antibody response that drove viral escape and coincided with a parallel evolution of their infecting quasispecies towards increasing infectious properties, increasing susceptibility to T20 and increasing resistance to both CD4 analogs and V3 loop-directed NAbs. This evolution was associated with identical Env sequence changes at several positions in the V3 loop, the fusion peptide and the HR2 domain of gp41. The common evolutionary pattern of Env in different hosts suggests that the capacity of a given Env to adapt to changing environments may be restricted by functional constraints that limit its evolutionary landscape.